PERUBAHAN STATUS N, P, K TANAH DAN HASIL TANAMAN JAGUNG MANIS (Zea mays saccharata sturt) AKIBAT PEMBERIAN PUPUK CAIR ORGANIK PADA ENTISOLS - Isrun Isrun (Universitas Tadulako, 2009)
The field experiment was conducted to study changes in total nitrogen, available phosphor, available potassium and sweet corn yield (Zea mays saccharata sturt) as a result of liquid organic fertilizer addition on Entisols of Poboya. The experiment was carried out from June to September 2007 in Poboya farm field of Palu. A Randomized Block Design (RBD) was used with two factorial experiment replicated three times. The first factor was liquid organic fertilizer of four levels: 0 cc l-1; 5cc l-1; 10 cc l-1 and 15 0 cc l-1. The second factor was various time of fertilizer application: applied twice at 4 and 8 weeks after planting; and three times at 3, 6 and 9 weeks after planting. The tested plant used was sweet corn. The results of the experiment showed that liquid organic fertilizer and application time significantly improved the soil chemical characteristics of Poboya Entisols and increased the sweet corn yield. A maximum result of 3.9 ton ha -1 sweet corn was observed in 15 ccl-1 liquid fertilizer treatment with application time of 3,6, and 9 weeks after planting.